THE EFFECTS OF FAMILIAR, UNFAMILIAR MUSIC AND AUDIOBOOKS EXPOSURE ON SPEECH PARAMETERS OF ELDERLY WITH ALZHEIMER’S DISEASE: A WITHIN CASE STUDIES - Ning, Fidelia Chan Xue; Mukari, Siti Zamratol Mai Sarah; Ahmad, Kartini (PEOPLE: International Journal of Social Sciences, 2016)
Alzheimer’s disease is a cognitive disorder common among elderly whereby neurode generation occurs rapidly as a result of decline in brain activity. There have been many studies linking music memory with cognition among patients with Alzheimer’s disease. However, the types of music exposed, the familiarity of the music and their effects on speech production is still not adequately explained. Improvement in speech can be demonstrated in alteration of several speech parameters. This multiple case study (n = 3), seeks to investigate the effects of familiar and unfamiliar music on the speech fundamental frequency (F0), intensity range, and speech rate of 3 elderly subjects with Alzheimer’s disease. The speech parameters after exposure to familiar and unfamiliar music were measured longitudinally over a period of 21 weeks. A listening task to an audiobook was treated as control. Data revealed that in all of these subjects, there was wide variability in performance with no common pattern for familiar music. However, for unfamiliar music, two subjects showed increase in their speech rate. The third subject showed increase in F0 range. It is suggested that there may be more to understand how familiar and novel stimuli influence speech production in patients with Alzheimer’s disease.